O sposobie konstruowania haseł w dawnych słownikach przekładowych (na przykładzie prac Łukasza Brzezwickiego) - Anna Lenartowicz-Zagrodna (Ksiegarnia Akademicka Publishing, 2018)
On the Method of Constructing Entries in Old Translation Dictionaries (Using the Example of the Works of Łukasz Brzezwicki) The birth of Polish-Latin lexicography has usually been associated with Cnapius, the author of Thesaurus Polonolatinograecus seu Promptuarium linguae Latinae et Graecae (1621), while the two lexicographers who worked before him tend to be forgotten. In 1596 Nicholas Volckmar published Dictionarium trilingue tripartitum ad discendam linguam Latinam, Polonicam et Germanicam accommodatum, and a few years later, on the basis of Volckmar’s work, Łukasz Brzezwicki composed two dictionaries: Synonyma latina ex variis authoribus collata Polonice et Latine (Cracow 1602) and Puerilia ex variis onomasticis excerpta et in usum iuventutis Polonae publicata (Cracow 1625). Although the list of words in the dictionaries of these two authors is nearly identical, Brzezwicki introduced several changes to his lexicographic method. One of the innovative features of Synonym… and Puerilia… is the construction of entries in the form of series of synonyms. The goal of the present paper is to analyse these series and to answer the questions: What kinds of pairs of words does Brzezwicki introduce? What role do they play? In what relation are those pairs to the state of contemporary Polish? This is the basis on which this paper will attempt to evaluate the level of lexicographic and linguistic awareness of Łukasz Brzezwicki.